Answer:
A
Step-by-step explanation:
This is how I write
y=kx+m
but I have seen some write it like this:
y=mx+b
Well both of them are the same thing, I'll use the first one because I'm more comfortable with it.
y=kx+m
To find out what k
[tex]k = \frac{y2 - y1}{x2 - x1} [/tex]
So you first need to choose two points.
I'll go for (0,-5) and (2,0)
[tex]k = \frac{0 - 5}{2 - 0} [/tex]
[tex]k = \frac{ - 5}{2} [/tex]
Now you could insert k into the equation and it will look like this.
[tex]y = \frac{ - 5}{2}x + m[/tex]
To find out what m is just pick one point and insert it into the equation. So if I pick (0,-5). 0=X therefore it should be replaced by x and -5=y therefore it should also be replaced by y.
[tex] - 5 = \frac{ - 5}{2} \times 0 + m[/tex]
m=-5
Try it with another point to see if you get the same answer. this time I'll pick (-6,10)
[tex] 10= \frac{ - 5}{2} \times( - 6)+ m[/tex]
m= -5
The equation will be y=-5/2x-5)